2014
DOI: 10.1111/zsc.12094
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of the ubiquitous coral reef crab subfamily Chlorodiellinae (Decapoda, Brachyura, Xanthidae)

Abstract: . Phylogenetic relationships of the ubiquitous coral reef crab subfamily Chlorodiellinae (Decapoda, Brachyura, Xanthidae). -Zoologica Scripta, 44, 165-178. The xanthid subfamily Chlorodiellinae is one of the most ubiquitous coral reef crab taxa in the Indo-West Pacific region. Many species are common in coral rubble and rocky shores from Hawaii to eastern Africa, often dominating reef cryptofauna in terms of biomass. Phylogenetic analyses of mitochondrial (COX1, 12S rRNA and 16S rRNA) and nuclear (histone H3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The greater phylogenetic resolution and higher support values recovered for Thalamitinae demonstrate that increased taxon sampling for other subfamilies should significantly improve future analyses of these groups. Yet results of this and other work also suggest that the molecular markers used here will likely never fully resolve deeper nodes in the family (e.g., see Lasley, Klaus & Ng, 2015 ; Thoma, Guinot & Felder, 2014 ).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The greater phylogenetic resolution and higher support values recovered for Thalamitinae demonstrate that increased taxon sampling for other subfamilies should significantly improve future analyses of these groups. Yet results of this and other work also suggest that the molecular markers used here will likely never fully resolve deeper nodes in the family (e.g., see Lasley, Klaus & Ng, 2015 ; Thoma, Guinot & Felder, 2014 ).…”
Section: Resultsmentioning
confidence: 74%
“…A total of 345 sequences from four molecular markers (16S rRNA, CO1, 28S rRNA, and H3) were generated from 114 portunoid species, 76 of which have never before been sequenced. Amplifications were carried out following protocols outlined in Evans & Paulay (2012) , Lasley, Klaus & Ng (2015) , and Leray & Knowlton (2015) . Typically this included the use of a “step-down” PCR profile ( Evans & Paulay, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is important to mention the findings of Lai et al (2011), who found that the two congeners Etisus electra and E. frontalis are very similar morphologically. As well, Lasley et al (2015) concluded from their molecular analyses and morphological observations that members of subfamily Etisinae are not monophyletic and need extensive revision. The results of the present study advance the molecular investigations of this group in the Red Sea by providing mitochondrial (COI, 16S) combined with nuclear (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, spoon-tipped chelae appear to be a mutual morphological character between some xanthin and etisine genera (Lai et al 2011), which can cause confusion in distinguishing between some genera for non-experts. However, some of these mutual characters, in addition to dactyl-propodal locks on the ambulatory legs (Sèrene 1984), have been discussed by others (Ng et al 2008;Lai et al 2011;Lasley et al 2015) as ways to distinguish between Etisinae and Chlorodielinae. The pairwise genetic distances (Table 3) between our specimens and a sequence from a specimen identified as Etisus laevimanus (KP163570, Hawaii) ranged from 3.7% to 4.2%, possibly indicating geographic genetic differences within the same species.…”
Section: Remarksmentioning
confidence: 99%